Fractal analysis of veins in Permian carbonate rocks in the Lingtanchang anticline, western China. Issue 2 (20th August 2013) - Deng, B.; Liu, S.; Jansa, L.; Yong, S.; Zhang, Z.
Abstract Statistical analysis of the thickness distribution of veins in the Lingtanchang structure, southern Sichuan basin, western China, indicates that vein thickness conforms to fractal character and a power‐law distribution, whereas various distributions of veins are indicated by both the spacing distribution and the Cv values. According to geometry and structure, the veins in the Lingtanchang structure can be divided into confined and through‐going veins. The statistical analyses show that confined intralayer veins are consistent with a power‐law distribution in thickness, with Dt values of 1.1–1.7 and a log‐normal distribution in spacing with Cv values of 0.8–0.9. The confined intra‐ to interlayer veins show Dt values of 1.0–1.3 and an exponential distribution in spacing, with Cv values of 0.9–1.0, indicating an unconnected vein network with weak ability for paleofluid flow. However, the through‐going veins show the lowest Dt values of 0.6–0.8 with a power‐law distribution in thickness and power‐law to exponential distribution in spacing with Cv values of 1.5–3.2. Differences in spacing distribution and in the thickness of veins can be explained by different stages of vein growth from confined to through‐going veins. Such processes are dominant with percolating cluster models, which significantly controls spatial distribution of veins and paleofluid flow, and therefore the reservoir conditions in the southern Sichuan basin.